Before Kukulkán : Bioarchaeology of Maya Life, Death, and Identity at Classic Period Yaxuná - Tiesler, Vera (Book collections on Project MUSE., 2017)
"A significant look at Maya life prior to Chichen Itzá during the Classic Period in the Yucatan"--Provided by publisher.